Pathology of geographical research (with an emphasis on rural geography research) - Naser Shafiei Sabet; Saber Sedighi (Pizhūhish/hā-yi Rūstāyī, 2018)
In recent decades, reduction of space to mere objectivity has created problems for the science of geography. One of the issues in the recognition of geographical space is reflected in the geographical research that is confined to purely quantitative methods. This paper is an attempt to have a pathological analysis of the principles of geographical knowledge (i.e. ontology, epistemology and methodology) with respect to the dominant paradigm of geographical research, in general, and in rural geography knowledge, in particular. A content analysis of 70 recent geographical articles (rural studies) showed that positivism has been the dominant approach in geographical research. Also, in 54 articles, the relationship between the researcher and the researched was identified to be a dichotomous subject-object relationship. The goal of this article is to seek an understanding of "language" as a starting point to examine the local actors' space. Along with language, there are other tools to contribute; questionnaires, statistical models, and software analysis techniques such as the GIS software are of benefit too in this respect.